2021
DOI: 10.1177/10422587211002185
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the Storm: How Foreign Aid and Institutions Affect Entrepreneurship Activity Following Natural Disasters

Abstract: This study examines how foreign aid and institutions affect entrepreneurship activity following natural disasters. We use insights from the entrepreneurship, development, and institutions literature to develop a model of entrepreneurship activity in the aftermath of natural disasters. First, we hypothesize the effect of natural disasters on entrepreneurship activity depends on the amount of foreign aid received. Second, we hypothesize that natural disasters and foreign aid either encourages or discourages entr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Moreover, aid allocated for the development of infrastructure boosts entrepreneurship and incentivized competition with homogeneous products. More recently, Boudreaux et al (2021) have found empirically that development aid mitigates the adverse effects of natural disasters on entrepreneurship.…”
Section: Other Possible Effects Of Development Aid Including Aft and ...mentioning
confidence: 99%
“…Moreover, aid allocated for the development of infrastructure boosts entrepreneurship and incentivized competition with homogeneous products. More recently, Boudreaux et al (2021) have found empirically that development aid mitigates the adverse effects of natural disasters on entrepreneurship.…”
Section: Other Possible Effects Of Development Aid Including Aft and ...mentioning
confidence: 99%
“…Moreover, the communication between various units is often problematic because these countries lack the infrastructure for collective action (Dixit 2009). Boudreaux et al (2021) find the quality of institutions moderates the effect of foreign aid on starting a new business after a disaster.…”
Section: Quality Of Governance Moderates the Relationship Between Nat...mentioning
confidence: 99%
“…sample period (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). Most studies, including ours, that attempt to quantify the intensity of the disasters use a measure based on the number of people affected, injured, or killed from ED-DAT (for example, see Loayza et al 2012;Klomp and Valckx 2014;Noy 2009;Boudreaux et al 2021). Therefore, we define the "intensity of natural disaster" as the sum of the total number of people affected, injured, and homeless due to a natural disaster.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Balavac and Pugh (2016, p. 284) are interested in transition countries and argue 'that improvements in institutional qualityespecially political institutionsattenuate output volatility'. Boudreaux et al (2021) maintain that the quality of government and economic freedom are important factors regarding the extent to which natural disasters affect entrepreneurship. Institutional quality, furthermore, has been found to moderate the impact of financial crises on economic growth (Furceri and Mourougane, 2012).…”
Section: Theory: Institutional Quality and Resilience To Crisesmentioning
confidence: 99%
“…Boudreaux et al . (2021) maintain that the quality of government and economic freedom are important factors regarding the extent to which natural disasters affect entrepreneurship. Institutional quality, furthermore, has been found to moderate the impact of financial crises on economic growth (Furceri and Mourougane, 2012).…”
Section: Theory: Institutional Quality and Resilience To Crisesmentioning
confidence: 99%